1988
DOI: 10.1073/pnas.85.2.497
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic membrane-cytoskeletal interactions: specific association of integrin and talin arises in vivo after phorbol ester treatment of peripheral blood lymphocytes.

Abstract: Members of the family of transmembrane integral membrane proteins called integrins have been implicated in forming attachments to actin microfflaments of the cytoskeleton. These attachments are thought to involve one or more intervening peripheral membrane proteins linked to integrin. To detect such possible linkages in vivo, the integrin molecules on the surfaces of intact chicken peripheral blood lymphocytes were collected into caps by cross-lnkin with specific antibodies, and the capped cells were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(80 citation statements)
references
References 27 publications
(35 reference statements)
2
77
1
Order By: Relevance
“…In addition, adhesion of these cells can be increased by PMA or the activating mAb KIM185, demonstrating that besides clustering of LFA-1 (avidity), affinity changes in the LFA-1 molecule (active conformation) are still required for strong binding to ICAM-1. These findings, along with data that integrins can associate with cytoskeletal components (a-actinin and talin), in particular through the 13-chain (Burn et al, 1988;Pavalko and LaRoche, 1993), led us to hypothesize that certain cytoskeletal proteins are essential to maintain LFA-1 in a high-avidity state on these cells. The observation that cytochalasin D, which inhibits actin polymerization, blocks the adhesion (in the absence of an activator of LFA-1) of the L cell, BLM transfectants, and IL-2/PHA-activated PBLs supports this hypothesis and demonstrates that this phenomenon is not leukocyte restricted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, adhesion of these cells can be increased by PMA or the activating mAb KIM185, demonstrating that besides clustering of LFA-1 (avidity), affinity changes in the LFA-1 molecule (active conformation) are still required for strong binding to ICAM-1. These findings, along with data that integrins can associate with cytoskeletal components (a-actinin and talin), in particular through the 13-chain (Burn et al, 1988;Pavalko and LaRoche, 1993), led us to hypothesize that certain cytoskeletal proteins are essential to maintain LFA-1 in a high-avidity state on these cells. The observation that cytochalasin D, which inhibits actin polymerization, blocks the adhesion (in the absence of an activator of LFA-1) of the L cell, BLM transfectants, and IL-2/PHA-activated PBLs supports this hypothesis and demonstrates that this phenomenon is not leukocyte restricted.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when LFA-1 is expressed on either hematopoietic or nonhematopoietic cells, adhesion to ICAM-1 can be induced by alteration in avidity (clustering) or affinity (induced by PMA or KIM185), whereas both avidity and affinity alteration cooperate to induce maximal adhesion. The importance of the association of cytoskeletal components (a-actinin and talin) with the ,32-chain has been reported previously (Burn et al, 1988;Pavalko and LaRoche, 1993). However, it is not known whether association with the cytoskeleton is important in modulating the affinity, the distribution of LFA-1, or both.…”
Section: Expression Of Lfa-1 By L Cell Fibroblasts and Blm Melanoma Cmentioning
confidence: 95%
See 1 more Smart Citation
“…The alpha and beta int¢grin subunits both contain a small cytoplasmic domain which can interact with the cytoskeleton matrix (10,11,37). Integrin-mediated binding to vitronectin and other matrix proteins is typically associated with integrin aggregation and cytoskeletal reorganization of microfilaments and microfilament-associated proteins, such as talin and vinculin (10,11). l-,s myoblasts bound to vitronectin were spread and displayed numerous projections typical of integrin-mediated binding to matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have demonstrated that the actin cytoskeleton can regulate integrin-mediated T cell adhesion (Burn et al, 1988). Inhibitors such as cytochalasin B and D (Cyt D) have been used to inhibit 2-and 1-mediated adhesion to their ligands (Rothlein and Springer, 1986).…”
Section: Tagln2 Controls Integrin-mediated T Cell Adhesionmentioning
confidence: 99%